An Advanced Systematic Literature Review on Spatiotemporal Analyses of Twitter Data. Issue 6 (18th March 2015) - Steiger, Enrico; de Albuquerque, João Porto; Zipf, Alexander
Abstract: The objective of this article is to conduct a systematic literature review that provides an overview of the current state of research concerning methods and application for spatiotemporal analyses of the social network Twitter. Reviewed papers and their application domains have shown that the study of geographical processes by using spatiotemporal information from location‐based social networks represent a promising and still underexplored field for GIScience researchers.